Anisotropy of mechanical properties and hardening mechanism in ZrO2–Y2O3 solid solution crystals - Mikhail А. Borik; Vasilij R. Borichevskij; Vladimir T. Bublik; Tatyana V. Volkova; Aleksej V. Kulebyakin; Elena E. Lomonova; Filipp O. Milovich; Valentina A. Myzina; Polina A. Ryabochkina; Sergei V. Seryakov; Nataliya Yu. Tabachkova (Modern Electronic Materials, 2017)
The anisotropy of the mechanical properties of crystalline ZrO2 – 2.8 mol.% Y2O3 solid solutions has been studied. The crystals have been grown by skull melting technique. The microhardness and fracture toughness for different crystallographic planes have been tested by indentation with different indenter diagonal orientations. We show that the microhardness of the material depends on the crystallographic orientation but slightly whereas the fracture toughness varies for different planes. The maximum fracture toughness has been observed in the specimen cut out from the crystal laterally to the <100> orientation. We have studied the microhardness anisotropy for different indenter diagonal orientations. The maximum fracture toughness has been obtained for the {100} plane and the <100> indenter diagonal orientation. The phase composition inside and outside the indents on the {100}, {110} and {111} surfaces for 20, 3 and 1 N loads has been studied using local Raman spectroscopy. The degree of the tetragonal-monoclinic transition has been assessed for different crystallographic planes and different indenter diagonal orientations. We show that the tetragonal-monoclinic transition is anisotropic, this affecting the transformation hardening mechanism. The maximum amount of the monoclinic phase has been detected in the vicinity of the indent in the {100} plane for the <100> indenter diagonal orientation. The highest fraction toughness has also been observed in {100} plane for the <100> indenter diagonal orientation. Probably, this indenter diagonal orientation provides for the maximum stress orientation along the coherent conjugation planes between the tetragonal and the monoclinic phases during the tetragonal-monoclinic transition, i.e. (100)t || (100)m and [001]t || [010]m.